Thermodynamic properties prediction of Mg-Al-Zn melts based on the Atom and Molecule Coexistence Theory (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
A developed and verified thermodynamic model based on the atom and molecule coexistence theory (AMCT) is employed to predict activities relative to pure liquids as standard state in Mg-Al, Mg-Zn, Al-Zn and Mg-Al-Zn melts through the calculated mass action concentrations of structural units, i.e., Ni According to AMCT, Ni can be extrapolated and worked out by the chemical equilibrium constant of a structural molecule, i.e., Ki, in the Mg-Al-Zn ternary system and binary subsystems, so that this paper has regressed and optimized the standard Gibbs free energy function with reported activities and mixing thermodynamic properties in Mg-Al, Mg-Zn and Al-Zn melts, then resulting in Ki and Ni deduced by Gibbs free energy function at studied temperature. The results of calculating thermodynamic-property in the full composition range for liquid Mg-Al-Zn from 880 to 1100 K, as well as Mg-Al from 923 to 1073 K, Mg-Zn from 880 to 973 K and Al-Zn from 1000 to 1073 K are present in the paper by coupling with Ni and AMCT. An excellent agreement is noticed between the calculated values of this study and measured thermodynamic data from the references, suggesting that the AMCT can be well applied to describe and predict the activities of the Mg-Al-Zn system and its subsystems.